Beliefs about global English and L2 motivation of Chinese EFL learners / Gu Huiyuan - Gu , Huiyuan (2023)
Beliefs about English as a Global Language held by Chinese EFL learners as well as their attitudes toward Global Englishes (GE) and English language teaching (ELT) have been widely explored in research literature (Fang & Ren, 2018; He, 2020). Recently, appeals have been made for the need of a solid framework to examine language learners’ beliefs in a GE-oriented context. However, few studies have focused on the Chinese EFL learners’ beliefs about English and Global Englishes in such a context. Also, there is a lack of studies that connect these beliefs to students’ L2 motivation. This thesis addressed this research gap. It explored EFL learners’ beliefs about English language and Global Englishes in mainland China. It employed the Theory of Planned Behavior (TPB) model as a theoretical framework. The research objectives were: (1) to explore Chinese EFL learners’ beliefs about Global Englishes and English language learning; (2) to examine the attitudes (behavioral beliefs), subjective norms (normative beliefs) and self-efficacy (control beliefs) that learners hold about English and English language learning; (3) to assess Chinese EFL learners’ motivation for L2 learning; (4) to identify the dimensions that underlie Chinese EFL learners’ beliefs and L2 motivation; (5) to investigate the relationship between Chinese EFL learners’ beliefs and their L2 motivational orientations. To meet these objectives, the study employed an explanatory (QUANQUAL) mixed-methods research design. Participants in this study were 460 (N = 460) students at a university in mainland China. The findings from the exploratory factor analysis revealed that the students’ beliefs formed four dimensions, namely, awareness of Global Englishes, beliefs about Standard English, beliefs about China English and beliefs about English language education. Notably, one dimension — beliefs about English language education — had a clear ideological orientation as it referred to how English should be taught. As for the students’ L2 motivation, three dimensions were identified, namely, (1) Integrative Orientation, (2) Instrumental Orientation and (3) International Posture. The regression analysis indicated that there existed positive and statistically significant relationships between some of the language learners’ beliefs and their L2 motivation. Particularly, the beliefs about English language education were found to have the strongest impact. The thematic analysis in the qualitative phase provided empirical support to the finding from the quantitative strand. This study and its findings have some theoretical, methodological and pedagogical implications.